1988
DOI: 10.1002/mus.880110809
|View full text |Cite
|
Sign up to set email alerts
|

Serum CK, calcium, magnesium, and oxidative phosphorylation in mdx mouse muscular dystrophy

Abstract: Serum creatine kinase (CK) activity, calcium (Ca) and magnesium (Mg) contents of skeletal muscle and isolated mitochondria, as well as oxidative phosphorylation of X-linked muscular dystrophic (mdx) mice were compared with normal control animals at ages 5, 10, and 23 weeks. Serum CK is elevated in mdx mice at all ages, with highest activities at 5 weeks. The Ca content of dystrophic skeletal muscle is increased at all ages, whereas no clearly abnormal trend in muscle Mg levels was observed. Noncollagen protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
41
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 16 publications
(1 reference statement)
9
41
0
1
Order By: Relevance
“…In accord with previous reports, the mdx mice did not show striking alterations in development [1,10], with their mean body weight even being increased compared with control mice at 6-7 months of age [30]. High activities of the muscular enzyme creatine kinase were present in the serum of mdx compared with control mice, as previously described [1,[31][32][33]. This measurement was used in our study to confirm the phenotype of each mouse.…”
Section: Discussionsupporting
confidence: 89%
“…In accord with previous reports, the mdx mice did not show striking alterations in development [1,10], with their mean body weight even being increased compared with control mice at 6-7 months of age [30]. High activities of the muscular enzyme creatine kinase were present in the serum of mdx compared with control mice, as previously described [1,[31][32][33]. This measurement was used in our study to confirm the phenotype of each mouse.…”
Section: Discussionsupporting
confidence: 89%
“…Although muscle fibers degenerate in the absence of myotubularin, sarcolemmal integrity remains mostly conserved, as opposed to several muscular dystrophies. Accordingly, blood levels of CK in Mtm1 KO mice are only slightly elevated in late stages of the disease, inflammatory infiltrates and fibrosis are absent in muscle, and regenerating myotubes are infrequent and nongrouped, which contrast with observations in mouse models of Duchenne muscular dystrophy (35,44) or in other dystrophic mice (36). These results suggest that myotubularin plays a role either in regulating signals from the extracellular compartment needed for muscle cell function or in preserving the internal architecture of myofibers.…”
Section: Discussionmentioning
confidence: 71%
“…It seems likely that the elevated protein turnover observed in mdx mouse muscles is a consequence of their being subject to a continued process of damage and repair, a suggestion which is supported by the histological observation of numerous degenerating and regenerating fibres in these muscles [14].…”
Section: Vol 268mentioning
confidence: 92%
“…Current evidence indicates that the increased intracellular Ca2+ content of mdx muscle fibres [14,15] may initiate the myopathic events. It has been demonstrated that the Ca2+ ionophore A23 187 causes increased proteolysis [16] and induces damage to muscle of normal mice and rats [17] through mechanisms which may involve activation of phospholipase enzymes [18].…”
Section: Vol 268mentioning
confidence: 99%